Rapid Pathotyping of Newcastle Disease Virus by Using Sybr Green Rt-pcr - Ainol Azifa Mohd Faik; Kenneth Francis Rodrigues; Syed Umar Faruq Syed Najmuddin; Vijay Subbiah Kumar; Siti Saidah Ag. Ahmad; Nieccorita Wong; Ag. Muhammad Sagaf Abu Bakar (Faculty of Science & Natural Resources, UMS, 2023)
Newcastle disease remains a significant threat to the global poultry industry, causing substantial economic losses. The etiological agent responsible for this disease is Newcastle Disease Virus (NDV), known for its varying pathogenicity in chickens. This research aims to develop a method for determining the pathotype of NDV from positive allantoic fluid samples originating from clinical cases through the utilization of Sybr green RT-PCR with melt-curve analysis targeting the fusion gene and comparing the result with conventional methods for NDV pathotyping and sequencing. Twentyfour clinical samples collected from various districts in Sabah from 2022 and 2023 were propagated in embryonated chicken eggs (ECE) and tested for mean death time (MDT). The amplification of the fusion genes in the samples was performed using conventional RT-PCR integrated with Sybr green dye. Subsequently, melt-curve analysis was conducted to differentiate between the various pathotypes of isolated NDV strains using a qPCR machine. Additionally, sequencing was carried out using another set of primers that amplify 700bp of the F region. The melt-curve study revealed that velogenic NDVs isolated from chicken samples were distinguished by a mean Tm of 84.14 ± 0.60 °C, while lentogenic NDV isolates exhibited a higher mean Tm of 87.44 ± 0.70 °C. These results showed good agreement with virus isolation using MDT. The fusion protein cleavage site showed a positive correlation between virulent and avirulent fusion motives. The method presented offers a rapid and efficient means of diagnosing and pathotyping NDV from allantoic fluid samples, eliminating the need for gel electrophoresis in PCR product analysis. In conclusion, this study demonstrates the effectiveness of Sybr green RT-PCR in combination with melt-curve analysis using a qPCR machine as a valuable and timeefficient approach for pathotyping different NDVs in clinical samples.